2002
DOI: 10.1073/pnas.242597199
|View full text |Cite
|
Sign up to set email alerts
|

Memory-specific temporal profiles of gene expression in the hippocampus

Abstract: Many experiments in the past have demonstrated the requirement of de novo gene expression during the long-term retention of learning and memory. Although previous studies implicated individual genes or genetic pathways in learning and memory, they did not uncover the collective behaviors or patterns of the genes. We have used genome-scale screening to analyze gene expression during spatial learning of rats in the Morris water maze. Our results show distinct temporal gene expression profiles associated with lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
146
1
3

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 174 publications
(164 citation statements)
references
References 51 publications
(45 reference statements)
14
146
1
3
Order By: Relevance
“…The MWM was chosen as a behavioral task because previous work by Cavallaro et al (2002) showed that it causes changes, that differ between the SC and WM mice, in the level of Htr2c mRNA during the 24 hours after the last exposure to swimming. Those experiments measured Htr2c mRNA levels in rat hippocampus by microarrays, and while not dramatic (the greatest was a four fold decrease), changes were significant.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The MWM was chosen as a behavioral task because previous work by Cavallaro et al (2002) showed that it causes changes, that differ between the SC and WM mice, in the level of Htr2c mRNA during the 24 hours after the last exposure to swimming. Those experiments measured Htr2c mRNA levels in rat hippocampus by microarrays, and while not dramatic (the greatest was a four fold decrease), changes were significant.…”
Section: Discussionmentioning
confidence: 99%
“…Such changes were not replicated here in mice by quantitative RT-PCR, but there are reasonable explanations. First, the protocol for the MWM used here differed slightly from that of Cavallaro et al (2002), specifically in that we included a probe trial for all mice, after the three blocks of training. Thus, the time of euthanasia was delayed until after an additional swimming episode beyond the learning phase.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations